Безпека бази даних у високо регульованих галузях - Ніколаєв, А. О.; Кривенко, С. А. (ХНУРЕ, 2025)
The document discusses the importance of database security in highly regulated industries, particularly focusing on the use of Amazon RDS and various methods to enhance data protection. Users must evaluate data confidentiality and ownership standards in compliance with current laws, especially in healthcare and finance sectors. Cloud technologies like AMAZON RDS provide new research opportunities. Amazon RDS is suitable for OLTP, efficiently handling large volumes of transaction data, such as banking transactions, by securely storing and updating transaction details. A variety of methods are recommended to manage access and enhance security for Amazon RDS, including using virtual private clouds, SSL/TLS connections, encryption, and database security features.
Keywords: безпека бази даних; високо регульована галузь